2017
DOI: 10.2166/washdev.2017.178
|View full text |Cite
|
Sign up to set email alerts
|

History of sanitation and hygiene technologies in the Hellenic world

Abstract: Sanitation and hygiene technologies have existed in ancient Hellas since the Bronze Age (ca. 3200–1100 bc), when extensive sewerage and drainage and other elaborate sanitary structures were known in Minoan palaces and towns. Classical and Hellenistic periods should be considered as the most progressive eras in the design of sanitary engineering. At that time anatomically shaped toilet seats are found in several sites since many private houses and public buildings have them. As cities grew in size the pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…What is even more interesting is the connection of water presence with theocratic concepts, superstitions, and processes in sacred complexes dedicated to gods with healing powers. Plutarch (Αιτίαι Φυσικαί), Vitruvius (De Architectura), Pliny (Naturalis Historiae), and Aristotle (Problems) express similar views on the effect of water quality on human health [5,6]. Alcmaeon of Croton, in the first half of the fifth century, was the first who mentioned that the health of people are very much connected to the quality of water (Aetius, V, 30, 1), which, according to Vitruvius (De Architectura I, 4, 9, 10), was examined by the senses, taste, smell, appearance, and temperature.…”
Section: Archaic Till Hellenistic Times 41 Water Quality and Human Hmentioning
confidence: 99%
See 1 more Smart Citation
“…What is even more interesting is the connection of water presence with theocratic concepts, superstitions, and processes in sacred complexes dedicated to gods with healing powers. Plutarch (Αιτίαι Φυσικαί), Vitruvius (De Architectura), Pliny (Naturalis Historiae), and Aristotle (Problems) express similar views on the effect of water quality on human health [5,6]. Alcmaeon of Croton, in the first half of the fifth century, was the first who mentioned that the health of people are very much connected to the quality of water (Aetius, V, 30, 1), which, according to Vitruvius (De Architectura I, 4, 9, 10), was examined by the senses, taste, smell, appearance, and temperature.…”
Section: Archaic Till Hellenistic Times 41 Water Quality and Human Hmentioning
confidence: 99%
“…Moreover, Pedanius Dioscorides, a Greek physician of the first century AD, suggested that a mixture of an equal measure of water and must (grape pulp) boiled over a soft fire until the water is used up has laxative effects for the human body. Talking about herbal medicine in his five-volume book De Materia Medica (5,13), he also mentioned that for the same purposes, someone can mix an equal amount of sea water, rainwater, honey, and must, pour it out into another jar, and set it in the sun for 40 days.…”
Section: Roman Eramentioning
confidence: 99%
“…Moreover, it can most certainly be concluded from the surviving remains that lavatories were used by many people simultaneously, despite their use almost two centuries after the official end of the ancient religion and the prevalence of Christianity which promoted privacy. During that period not only single seat toilets are constructed in old buildings [70], promoting privacy, but also single bathing chambers are incorporated in preexisting Roman baths, which originally had only common bathing pools, as in Epidauros [71]. Construction wise these toilets were supplied by water through pipes or the ditch system of the bath, possibly reusing water out of the main use of the bath as well.…”
Section: The Byzantine Practices (4th-14th C Ad)mentioning
confidence: 99%
“…During that period not only single seat toilets are constructed in old buildings [70], promoting privacy, but also single bathing chambers are incorporated in preexisting Roman baths, which originally had only common bathing pools, as in Epidauros [71].…”
Section: The Byzantine Practices (4th-14th C Ad)mentioning
confidence: 99%
“…Ecosan innovation has advanced in different geographical settings (Angelakis 2017). The period from 1800 to 1965 signified the age of sanitation alignment and technological advancement worldwide (Yannopoulos et al 2017). The concept of Ecosan, however, first appeared in the 1990s as new sanitation millennium agenda (Hu et al 2016).…”
Section: Introductionmentioning
confidence: 99%